2021
DOI: 10.3390/rs13142699
|View full text |Cite
|
Sign up to set email alerts
|

Water Mixing Conditions Influence Sentinel-2 Monitoring of Chlorophyll Content in Monomictic Lakes

Abstract: Prompt estimation of phytoplankton biomass is critical in determining the ecological quality of freshwaters. Remote Sensing (RS) may provide new opportunities to integrate with situ traditional monitoring techniques. Nonetheless, wide regional and temporal variability in freshwater optical constituents makes it difficult to design universally applicable RS protocols. Here, we assessed the potential of two neural networks-based models, namely the Case 2 Regional CoastColour (C2RCC) processor and the Mixture Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Relatively lower can be 𝑅 2 𝑅 2 attributed to the 8-day difference between the satellite overpass and field survey dates and the occurrence of a tropical depression within that timeline. Perrone et al (2021) found no negative effect on the accuracy of their predictive models using such a time window, however, only under stable weather conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Relatively lower can be 𝑅 2 𝑅 2 attributed to the 8-day difference between the satellite overpass and field survey dates and the occurrence of a tropical depression within that timeline. Perrone et al (2021) found no negative effect on the accuracy of their predictive models using such a time window, however, only under stable weather conditions.…”
Section: Discussionmentioning
confidence: 88%
“…Table 4 provides examples of operational DCs initiatives around the globe related to the water ecosystem, proving that the big data management is not an excuse for not using new technologies when there are existing tools that are being applied with great success. Our work highlighted the recent trend to use EO big data processing platforms that are also able to execute user-defined algorithms by the various research groups which was difficult to deploy on the existing geographical information systems as a simple plugin, such as the Semi-automatic Classification Plugin [88].…”
Section: Yearmentioning
confidence: 99%
“…Currently, various optical satellite imaging systems have been utilized for estimating Chla, including the Coastal Zone Colour Scanner (CZCS) (Conkright et al, 2003), Seaviewing Wide Field Sensor (SeaWiFS) (Gholizadeh et al, 2016), Medium Resolution Imaging Spectrometer (MERIS) (Moses et al, 2012;Augusto-Silva et al, 2014), Moderate Resolution Imaging Spectroradiometer (MODIS) (Ogashawara et al, 2014;Li et al, 2019), Geostationary Ocean Colour Imager (GOCI) (Kim et al, 2016), Ocean and Land Colour Instrument (OLCI) (Werther et al, 2021;Kravitz et al, 2020), Landsat 8 OLI (Kuhn et al, 2019;Pu et al, 2019;Cao et al, 2020), and Sentinel-2 (S2) (Sent et al, 2021;Ogashawara et al, 2021;Niroumand-Jadidi et al, 2021). Among the numerous optical satellite datasets available, Sentinel-2B MSI (S2B) data have garnered recognition as a promising tool for Chla retrieval in inland waters (Niroumand-Jadidi et al, 2021;Perrone et al, 2021). The selection of this sensor is primarily motivated by its temporal coverage (10 days), spatial resolution (up to 10 meters), and easy accessibility.…”
Section: Introductionmentioning
confidence: 99%